Exploring the adoption of diaphragm and lung ultrasound (DLUS) by physiotherapists, physical therapists, and respiratory therapists: an updated scoping review - Hayward, Simon; Cardinael, Camella; Tait, Chloe; Reid, Michael; McCarthy, Andrew (The Ultrasound Journal, 2025)
Background: The adoption of diaphragm and lung ultrasound (DLUS) by physiotherapists, physical therapists, and respiratory therapists (“therapists”) to examine and assess the diaphragm and lungs continues to grow. The aim of this updated scoping review is to re-explore and re-collate the evidence around the adoption of DLUS by therapists.Methods: This scoping review followed the PRISMA-ScR guidelines. Data sources searched included AMED, EmCare, CINAHL, Embase, Medline, PubMed and Pedro. Grey literature sources were searched alongside communication with leading authors in the field. The Participants, Concept and Context (PCC) approach was employed to formulate the research question. A charting form was developed and piloted to extract: title, authors, year of publication, country of origin, professional group involved (population), lung or diaphragm ultrasound (concept), evaluation method, educational, clinical or research setting (context), subject/disease/patient group, sample size, study design and professional group performing DLUS.Results: 133 studies met all inclusion criteria, an increase of 107 new studies compared to the original scoping review searches 7-years ago. Studies were included from 17 new countries and included 17 new participant populations. Lung ultrasound saw the largest increase in study number with education and implementation emerging as a new area of investigation. Full list of included studies is provided in Supplementary File 1.Conclusion: The number of DLUS studies involving therapists continues to show international growth with studies investigating an increasing range of participant populations. Published studies now include research on DLUS adoption, implementation, and utility amongst all three of the therapy professions who use DLUS. The potential of DLUS and its direct impact on patient outcomes still needs to be explored further. However, DLUS remains a novel and innovative imaging technique in the hands of physiotherapists, physical therapists, and respiratory therapists as its utility continues to grow in various research, clinical and educational settings.